Intoxicação em búfalos (Bubalus bubalis) por Baccharis megapotamica var. weirii - Oliveira Filho, Jose Carlos de (2012)
In the first part of the thesis, the spontaneous occurrence of an outbreak of Baccharis megapotamica var. weirii poisoning in buffalo in the Central region of the State of Rio Grande do Sul is reported. Ten out of 50 buffalo died 24 48 hr after being introduced into a pasture containing abundant amounts of the plant. Factors influencing the ingestion of the plant and consequent toxicosis included hunger, stress caused by shipment, and unfamiliarity with the plant. Clinical signs included serous ocular discharge, incoordination, mild bloat, and muscle trembling. One buffalo was necropsied. Gross findings included dehydration, abundant liquid in the rumen, reddening of the mucosa of forestomachs, abomasum, and intestine, and edema of the wall of the rumen. The main histologic lesions were superficial to full thickness degeneration and necrosis of the stratified epithelium lining the forestomachs, necrosis of the intestinal mucosa, and widespread lymphoid necrosis. A calf (Bos taurus) was fed a single dose of 5 g/kg/body weight of B. megapotamica var. weirii harvested from the same site where the buffalo died. Twenty hours after the administration of the plant this calf died with clinical signs and lesions similar to those observed in the naturally poisoned buffalo.sido consumida pelos búfalos. In the second part of the thesis, Five male 6-8 month-old Murrah buffalo calves were orally dosed with the fresh aerial parts of Baccharis megapotamica var. weirii at doses of 1, 3, 4, 5 and 10 g/kg body weight (bw) (~1-10 mg macrocyclic trichothecenes/kg/bw). The B. megapotamica used for the experiment was harvested on a farm where a recent spontaneous outbreak of poisoning caused by such plant had occurred. Clinical signs appeared 4-20 hours and 4 buffalo died 18-49 hours after the ingestion of the plant. Clinical signs were apathy, anorexia, and watery diarrhea, fever, colic, drooling, muscle tremors, restlessness, laborious breathing and ruminal atony, and dehydration. The most consistent gross findings were restricted to the gastrointestinal (GI) tract consisted of varying degrees of edema and reddening of the mucosa of the fore-stomachs. Histopathological findings consisted of varying degrees of necrosis of the epithelial lining of the fore-stomachs and of lymphocytes within lymphoid organs and aggregates. Fibrin thrombi were consistently found in sub-mucosal vessels of the fore stomachs and in the lumen of hepatic sinusoids. It is suggested that dehydration, septicemia and disseminated intravascular coagulation participate in the pathogenesis of the intoxication and play a role as a cause of death. A subsample of the B. megapotamica var. weirii was frozen-dried and ground and analyzed using UHPLC (Ultra High Performance Liquid Chromatography) with high resolution Time of Flight mass spectrometry and tandem mass spectrometry, it was shown that the plant material contained at least 51 different macrocyclic trichothecenes at a total level of 1.1-1.2 mg/g. About 15-20% of the total trichothecenes contents was found to be monosaccharide conjugates, with two thirds of these being glucose conjugates and one third constituted by six aldopentose conjugates (probably xylose), which has never been reported in the literature.